Design of an Aerospace Langmuir Probe Volt-ampere Characteristic Load Simulator. Issue 1 (1st June 2022) - Zhao, Zhendong; Wang, Yi; Zhou, Ying; Chen, Guangfeng; Hu, Xiangyu; Zhang, Haiyan
Abstract: The development process of space Langmuir probe needs to complete a large number of tests and calibration tests on the ground. Due to the long calibration period, complexity and high cost of plasma environment calibration, calibration tests are usually carried out after the instrument has been developed, in order to conduct preliminary tests on Langmuir probe during the instrument development process to verify the performance, as well as to save the cost of calibration tests and increase the reliability of the instrument, An advanced spatial Langmuir probe volt-ampere(I-V) load simulator was designed in this paper. Based on the positive and negative polarity of the external bias voltage, the I-V characteristic curve of the Langmuir probe was divided into positive and negative characteristic curves, which were realized by the combination of the output characteristic curves of NPN and PNP transistors, and the diode switching selectivity. The laboratory test results were consistent with the theoretical curve, verifying the validity and compliance of the design, which can play an important role in supporting the development of the space Langmuir probe and the calibration of the plasma environment.